Anti-nociceptive activity of triterpenes from Ardisia sp. (Subgenus Tinus) - Diezmos, Marie Luciene S. (Animo Repository, 2011)
A mixture of triterpenes composing of α-amyrin, β-amyrin and bauerenol (ASPS) isolated from the leaves of Ardisia sp. (Subgenus Tinus) was tested for its anti-nociceptive property using hot plate, tail flick and the acetic acid writhing assays. Results from the hot plate assay indicate that three doses (5, 10, 50 mg/Kg BW) revealed a relatively higher analgesic activity (26.56±7.17%, 21.28±29.63%, and 21.25±13.63% respectively compared to the positive control (16.98±32.88%) at 75 minutes post treatment. ASPS has no effect in the tail flick assay at 5 mg/Kg BW, 10 mg/Kg BW and 50 mg/Kg BW at 30 and 75 minutes post treatment. ASPS however was found most effective in the acetic acid writhing assay where the lowest dose had the least number of abdominal writhing frequency with the highest % anti-nociceptive effect at 5 mg/Kg BW (72.32± 17.69% and 70.19±29.93% respectively) in both male and female mice similar to the effects of Diclofenac (61.58± 20.43% and 59.87±39.19% respectively). ASPS exhibits potential as an anti-nociceptive substance for development of alternative drugs.